Rural ICT policy: Democracy of technology - Okello, Dorothy (Technical Centre for Agricultural and Rural Cooperation, 2011)
Uganda's decentralisation policy has led to the development of wireless broadband services in all of the country's districts. Cooperation between the government, NGOs, businesses and individuals will be essential to give everyone equal access to ICTs.